2015
DOI: 10.4274/mirt.76476
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Medicine in Thyroid Diseases in Pediatric and Adolescent Patients

Abstract: Both benign and malignant diseases of the thyroid are rare in the pediatric and adolescent population, except congenital hypothyroidism. Nuclear medicine plays a major role, both in the diagnosis and therapy of thyroid pathologies. Use of radioactivity in pediatric population is strictly controlled due to possible side effects such as secondary cancers; therefore, management of pediatric patients requires detailed literature knowledge. This article aims to overview current algorithms in the management of thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 117 publications
(171 reference statements)
0
18
0
Order By: Relevance
“…There are certain echographic characteristics such as echogenic behavior of the thyroid nodule (as purely cystic or hyperechoic nodules), good demarcation and external vascularization suggesting signs of benign course (e.g., a thyroid adenoma). On the contrary, solid hypoechogenic nodules, irregular borders, internal vascularization, presence of microcalcifications or recent increase in size on follow-up are associated with malignancy [10].…”
Section: Diagnostic Methods In the Evaluation Of Hyperthyroidismmentioning
confidence: 99%
See 3 more Smart Citations
“…There are certain echographic characteristics such as echogenic behavior of the thyroid nodule (as purely cystic or hyperechoic nodules), good demarcation and external vascularization suggesting signs of benign course (e.g., a thyroid adenoma). On the contrary, solid hypoechogenic nodules, irregular borders, internal vascularization, presence of microcalcifications or recent increase in size on follow-up are associated with malignancy [10].…”
Section: Diagnostic Methods In the Evaluation Of Hyperthyroidismmentioning
confidence: 99%
“…Ultrasound is, therefore, an image modality from which morphological information of the thyroid gland is obtained. On the other hand, thyroid scintigraphy is a functional imaging test that visualizes the distribution of active thyroid tissue and is used as a complementary test for definite diagnosis [6,10].…”
Section: Diagnostic Methods In the Evaluation Of Hyperthyroidismmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Archier et al ( 25 ) has also revealed that 18 F-DOPA PET/CT was reliable for a compartment based approach in lymph node involvement. Gallium-68 labeled peptides are also under scope for this use, especially to identify patients with tumors positive for somatostatin receptors, and thus candidates for radionuclide therapy ( 26 , 27 ). 18 F-FDG PET/CT should not be considered as the first step in the diagnostic algorithm and must be spared for the cases with elevated levels of tumor markers but negative conventional imaging examinations.…”
Section: Medullary Thyroid Cancermentioning
confidence: 99%